The Influence of Dividend Policy, Debt Policy and Share Prices on Company Size in the Jakarta Islamic Index (JII) - Nidya Lestari; Rika Lidyah; Peny Cahaya Azwari (Institut Agama Islam (IAI) Al-Qolam, 2023)
This research aims to determine the effect of dividend policy, debt policy and share prices on company size. The background of this research is because there are differences in the results of previous research between variables, so it is important to do re-research with samples from the latest period, that is 2017 to 2022. The research uses quantitative analysis sourced from secondary data. Based on the attachment to BEI announcement No PENG-00302/BEI.POP/11-2022, the population in this research is 30 companies. The sample selection used was a purposive sampling method and 7 companies were obtained from shares of companies listed on the Jakarta Islamic Index (JII). The analysis technique used is multiple linear regression analysis test. In this research, dividend policy influences company size. Any increase in company size can increase dividend payments assuming other variables remain constant. Debt policy has a significant effect on increasing company size. Then as the company size increases the debt policy will increase. Share prices have no effect on increasing company size